EFEKTIFITAS YOGA TERHADAP NYERI PUNGGUNG PADA IBU HAMIL - Riani " Silalahi; Misrawati " "; Oswati " Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research was to determine the effectiveness of yoga for back pain during pregnancy. Design of this study was “Quasy- experiment” and used “Non – equivalent control group”. This research was conducted at Puskesmas Harapan Raya and Sidomulyo that consist of 34 respondents which divided into two groups. The first group was experimental group and the second group was control group. The sampling used “purposive sampling”, the measurent instruments used numeric rating scale. The analysis used univariate and bivariate analysis by using Mann Whitney and Wilcoxon. The results showed there was a significant reduction of back pain during pregnancy after given yoga exercise with p value (0.00) < α (0.05). The result of the research is expected to be an alternative to reduce the intensity back pain of during pregnancy. Keywords              : alternative therapies, experiment, pregnancy, back pain, yoga